Pengaruh Kompensasi, Motivasi dan Disiplin Kerja Terhadap Kepuasan Kerja Karyawan - Tanuwijaya, Michael; Mulyono, Herry; Purnama, Benni; Benediktus Rolando (Journal of Trends Economics and Accounting Research, 2024)
Growth and progress in every company depends on the quality of the workforce it has. The role of human resources as the main driver of company policies and operational activities makes it a valuable asset for every business entity. This research aims to examine how compensation, motivation and work discipline influence employee job satisfaction at CV. Dharma Abadi Jambi City. This work was written using a quantitative type and The collected data is distributed via Google form in the questionnaire. The population taken was all employees CV. Dharma Abadi in Jambi City numbered 57 people using the census technique as a technique for taking the sample population. Research tools in analyzing data using SPSS v26. The research findings show that compensation, motivation and work discipline partially or simultaneously influence employee job satisfaction at CV. Dharma Abadi Jambi City.